The way, way back [videorecording (DVD)] - Faxon, Nat; Rash, Jim, 1970-; Collette, Toni; Peet, Amanda, 1972-; Janney, Allison; Rockwell, Sam; Carell, Steve, 1962-; Rudolph, Maya; Robb, AnnaSophia, 1993-; Janney, Allison (20th Century Fox Home Entertainment, 2013)
While fourteen year old Duncan is being dragged on a family trip with his mom and her overbearing boyfriend, he finds a gregarious friend at a local water park. The two form a powerful bond as Duncan learns to swim through the challenges of life, love, family and friendship, resulting in a vacation he'll never forget.